Adaptive sampling approach for volumetric shadows in dynamic scenes. Issue 8 (1st November 2013) - Lin, Hsiang‐Yu; Chang, Chin‐Chen; Tsai, Yu‐Ting; Way, Der‐Lor; Shih, Zen‐Chung
Abstract : Ray marching is an important technique to generate volumetric lighting effects. However, it is very expensive for each pixel on the screen, especially in dynamic scenes. The authors propose an adaptive approach to reduce samples for volumetric shadows in the time domain. In dynamic scenes, shadow volumes of moving objects are created and are rasterised to decide pixels that cannot be reused. The authors use a stencil buffer to maintain the information of screen pixels by recomputing or just using the previous information. Experimental results show that the proposed approach is simple to implement. Moreover, compared to the previous method, the proposed approach achieves a specific speedup and maintains similar visual quality.